Creating Tunable Mesoporosity by Temperature‐Driven Localized Crystallite Agglomeration. Issue 7 (10th January 2022) - Jeong, Seok; Sim, Youjung; Kim, Jin Kyun; Shin, Sunyoung; Lim, Jaewoong; Seong, Junmo; Lee, Seonghwan; Moon, Dohyun; Baek, Seung Bin; Kim, Chae Un; Ryu, Ja‐Hyoung; Lah, Myoung Soo
Abstract: A new synthetic approach for tunable mesoporous metal–organic frameworks (MeMs) is developed. In this approach, mesopores are created in the process of heat conversion of highly mosaic metal–organic framework (MOF) crystals with non‐interpenetrated low‐density nanocrystallites into MOF crystals with two‐fold interpenetrated high‐density nanocrystallites. The two‐fold interpenetration reduces the volume of the nanocrystallites in the mosaic crystal, and the accompanying localized agglomeration of the nanocrystallites results in the formation of mesopores among the localized crystallite agglomerates. The pore size can be easily modulated from 7 to 90 nm by controlling the heat treatment conditions, that is, the aging temperature and aging time. Various proteins can be encapsulated in the MeM, and immobilized enzymes show catalyst activity comparable to that of the free native enzymes. Immobilized β‐galactosidase is recyclable and the enzyme activity of the immobilized catalase is maintained after exposure to high temperatures and various organic solvents. Abstract : A tunable mesoporous metal–organic framework is synthesized through heat treatment of a highly mosaic crystal with low‐density crystallites, where the localized agglomeration of crystallites with reduced crystallite volume in the mosaic crystal produces mesopores among the localized crystallite agglomerates. The mesopores easily controlled by heat treatment condition can be used for enzyme immobilization.